Quality of nursing records in a hospital: audit (Research, Society and Development, 2021)
Objective to evaluate, through auditing, the effectiveness of nursing records in a public hospital in Goiás. Method This is a descriptive and analytical study, carried out on medical records of patients hospitalized in a public hospital in Goiás. hospital stay longer than five days in neonatal, pediatric and maternal intensive care units. For data analysis, we used the comparison of means of continuous variables through the Mann-Whitney test. Results it was verified that the inadequate filling of the medical records compromised the quality criteria, before and after the educational action. However, the means inherent to complete, incomplete and unfilled information in relation to medical records were significantly repaired after the educational action (p